The Management Dimensions of Entrepreneurship Education in Agribusiness Vocational School (A Case Study in SMKN 1 Bawen and SMK SPMAN Ungaran) - Marliyah, Lili (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: The problem especially in the field of vocational education was the weak relationship between the quality of graduates from educational institutions and the demand for employment opportunities. Purpose: This research aimed to define and examine the role of entrepreneurship education in the formulation, implementation and evaluation of agribusiness degree programs in vocational schools. Design/methodology/approach: This research used post hoc qualitative methodology, purposive sampling strategy, and interactive models in analyzing the data. Findings/Result: From the case study, it was found that there was a lack of integration between initiators of entrepreneurial soft skills (principals, principals, principals), and teachers of subjects other than entrepreneurship, according to research. This means that traditional and semi-modern teaching methods are still used in planning, implementing and evaluating learning. In accordance with this issue, it is necessary to develop integrated entrepreneurship education that relies on soft skills and competency-based training (CBT). So that it can improve the quality of graduates in creating students with an entrepreneurial spirit at the level of personal maturity, achieving student competency, reducing the gap in workforce needs, reducing the unemployment rate and increasing the number of entrepreneurs who will strengthen the national economy.Conclusion: This research adds to the literature on efforts to develop curriculum-based competencies and the use of learning methods that continue to develop to facilitate the acquisition of sustainable entrepreneurial knowledge and skills.Originality/value (State of the art): Its originality lies in its contribution to the literature on the management dimensions of economic education, because it uses management dimensions to analyze the conditions and efforts that must be made in vocational schools and the world of education needs to be involved in entrepreneurial management governance, especially in vocational schools to ensure implementation is in accordance with entrepreneurial practices as well as refinement of new learning that continues to develop. Keywords: competency-based training, entrepreneurship education, entrepreneurship, vocational education